A Proposal for an Accessible Videoconferencing Interface for People with Hearing Impairments - Lima, Matheus; Lemos, Guido; Kulesza, Raoni (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Sign languages (LS) are the natural form of communication between deaf people. However, although sign languages are recognized in many countries as a language, access to information and education is still a common problem for deaf people. In Brazil, despite the existence of several accessibility laws that determine support for deaf people, many are still dependent on Libras interpreters to communicate, which impairs their autonomy. As a result, there is a great difficulty for the deaf to exercise their citizenship and have access to quality information and education through sign languages, which generally implies linguistic delay and knowledge acquisition. In this sense, the present work addresses a proposal for an accessible interface of tele-education for the hearing impaired in order to facilitate access to information, making it possible to bring the figure of the remote interpreter to the classroom. This solution involves adapting the interface of the open source system, making it possible for the remote interpreter to be present to meet the needs of deaf students and make the classroom experience more accessible. In addition, a solution for displaying live subtitles was also implemented. The results obtained in this study proved to be promising, with 50% of users successfully completing more than 93.33% of the requested tasks. In addition, the group with the proposed solution was less dispersed when compared to the other group, concentrating most of its results above 80%, in a way that leads to believe that this type of adaptation can be welcomed by deaf users in the context of tele-education.